STYLISTIC CHANGES IN THE PROCESS OF TRANSLATION AND THEIR ORIGIN - Xudoyberganova Durdona Ismail’s daughter (American Journals Publishing, 2024)
This article focuses on stylistic changes in the example of Daniel Defoe’s The Life and Adventures of Robinson Crusoe. Examples given in two languages throughout the article allow understanding the new types of stylistic transformation.
Keywords: Translation, translator, text, origin, example, transformation, author, simila, consonance, imagery, hyperbole.